Delamination and Separation of Aluminum-Polyethylene-Paper Packing Material - Wang, Hui; Wang, Chongqing; Liu, Qun; Luo, Chengcheng; Jia, Fangfang; Meng, Xiangrui (Journal of Research Updates in Polymer Science, 2014)
Delamination and separation of laminated aluminum- polyethylene-paper packaging material were conducted for recycling packaging materials. Delamination was carried out using glacial acetic acid (GAA) solution. L9 (34) orthogonal experiments demonstrate that the most significant factor is GAA concentration followed by temperature and liquid/solid ratio. The delamination time decreased sharply with increasing temperature and the GAA concentration. The packaging material was delaminated under conditions of 60 ˚C, 70 v% GAA solution, liquid/solid ratio 20:1 and delamination time 60 min, and separation of polyethylene, paper and aluminum foil was conducted through sink-float method and air separation. Polyethylene, paper and aluminum foil were separated efficiently. The recovery and purity of aluminum foil was 90.81% and 100%, respectively; the purity of polyethylene was 100%; the recovery and purity of paper was 100% and 96.03%, respectively. This study offers some technical insights for recycling of aluminum-plastic packaging.